CONSUMER PUBLIC OPINION THROUGH INFLUENCER CONTENT ON TIKTOK: A CASE STUDY OF STUDIOSAJA ON THE @dunianadia ACCOUNT - Dini Amalia Hasibuan; Anang Anas Azhar (Journal Analytica Islamica, 2026)
The development of TikTok as a digital promotional space has shifted consumer public opinion formation from one-way message exposure to two-way interactions in the comments section. This study aims to analyze how consumer public opinion is formed through influencer content on the TikTok account @dunianadia discussing StudioSaja services. The study used a descriptive qualitative approach by analyzing 294 comments on a single relevant uploaded video, supported by literature on influencer marketing, digital communication, and agenda setting. The results show that audience responses are concentrated in three main tendencies: seeking further information about prices, locations, and photo results; expressions of interest in the service; and testimonials from users who have used StudioSaja services. In addition, the practice of tagging friends shows that the comments section is not only a space for responses but also a vehicle for interpersonal information dissemination. The novelty of this study lies in its positioning of the TikTok comments section as an arena for digital public opinion formation, not simply as a complement to promotional content. Theoretically, these findings expand the application of agenda setting in social media by showing that influencers not only direct audience attention through videos but also trigger the reproduction of issues in comment interactions. Practically, this study emphasizes the importance of information transparency in promotional content to build trust and encourage consumer engagement.